SAT0420 Ground Reaction Forces in Patients with Knee Osteoarthritis after Intra-Articular Treatments. (10th June 2014) - Garrido-Castro, J.L.; Gil-Cabezas, J.; Perez-Guijo, V.; Gonzalez-Navas, C.; Font-Ugalde, P.; Collantes-Estevez, E.
Abstract : Background: Osteoarthritis of the knee (OA) is the most common disease affecting the musculoskeletal system and one of the most important causes of disability among elderly population. Patients are assessed by questionnaires whose response may be influenced to some subjectivity (WOMAC, VAS, SF36). Gait analysis and ground reaction forces (GRF) produce objective and quantitative results of patient status with well-defined patterns. Vertical force curves are characterized by showing two peaks and a valley, showing a graph like an inverted W. Intra-articular injections of hyaluronic acid for the treatment of knee OA have been shown to reduce pain and improve joint function. In this work we have used GRF as evaluation tool in patients with knee OA before and after applying intra-articular treatments. Objectives: To analyze ground reaction forces in patients with knee OA before and after intraarticular treatment. Methods: 26 patients with knee OA (57.68±8.06 years, 1.65±0.88 m, 87.74±13.06 kg) with a high level of affectation (grade II-III according to Kellgren and Lawrence scale) and 6 healthy subjects as control group with similar characteristics (55.33±5.07 years, 1.70±0.77 m, . 88.52±10.15 kg) were analyzed. Intraarticular injections of hyaluronic acid were applied to patients before and after measurements (one and three months). Vertical, mediolateral and anteroposterior GRF were evaluated using a triaxial force plate (Bertec ® FP4060) Results: GRF in three axis and some temporary values as support time and first peak time in vertical force are showed in table. Significant differences between patients and control group in almost all parameters analyzed were found, showing a biomechanical altered gait. Regarding treatment sensitive measures, we could highlight first time peak in vertical force, force in the valley and difference between peak and valley. Sensitive measures also appear in the other two axis with larger braking and impulse forces. Also a shorter support time appears. Conclusions: Our study shows that GRF clearly improved approximating to values obtained for control group after intraarticular treatment. The evaluation of GRF in gait could be used as an evaluation tool, not only to demonstrate the biomechanical alteration produced by knee OA, but also as a tool for evaluating the effectiveness of treatment. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3313